(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe changes in plasma Matrix Metalloproteinase-9 concentrations in patients with chronic obstructive pulmonary disease in and out of exacerbation at 103 Military Hospital in 2023. Subjects and methods: A case-control study on 35 COPD patients treated inpatients at the Respiratory Center, Military Hospital 103 and 30 healthy people. Quantification of plasma MMP-9 levels by using ELISA technique. Results: There was no difference between plasma MMP-9 concentrations in COPD patients in and out of exacerbations, compared to healthy groups (p > 0.05). Plasma MMP-9 concentrations during exacerbation increased significantly in the group of patients with increased white blood cell counts (p < 0.001). Patients treated by corticosteroids before admission had lower plasma MMP-9 concentrations than the group without corticosteroids treatment (p < 0.001). Plasma MMP-9 concentrations in COPD patients after the exacerbation increased significantly in current smokers, comparing with current non-smokers (p < 0.001). After the exacerbation, patients with COPD type PP had a median plasma MMP-9 concentration of 61.2 ng/mL, significantly higher than patients with COPD type BB (p = 0.009). Conclusions: In the exacerbation, plasma MMP-9 concentrations were higher in patients with increased white blood cell counts and lower in patients using corticosteroids. After the exacebation, plasma MMP-9 concentrations were higher than in patients who had COPD type PP and were current smokers.